Movement velocity as a measure of exercise intensity in three lower limb exercises. Issue 12 (17th June 2016) - Conceição, Filipe; Fernandes, Juvenal; Lewis, Martin; Gonzaléz-Badillo, Juan José; Jimenéz-Reyes, Pedro
ABSTRACT: The purpose of this study was to investigate the relationship between movement velocity and relative load in three lower limbs exercises commonly used to develop strength: leg press, full squat and half squat. The percentage of one repetition maximum (%1RM) has typically been used as the main parameter to control resistance training; however, more recent research has proposed movement velocity as an alternative. Fifteen participants performed a load progression with a range of loads until they reached their 1RM. Maximum instantaneous velocity ( V max ) and mean propulsive velocity (MPV) of the knee extension phase of each exercise were assessed. For all exercises, a strong relationship between V max and the %1RM was found: leg press ( r 2 adj  = 0.96; 95% CI for slope is [−0.0244, −0.0258], P  < 0.0001), full squat ( r 2 adj  = 0.94; 95% CI for slope is [−0.0144, −0.0139], P  < 0.0001) and half squat ( r 2 adj  = 0.97; 95% CI for slope is [−0.0135, −0.00143], P  < 0.0001); for MPV, leg press ( r 2 adj  = 0.96; 95% CI for slope is [−0.0169, −0.0175], P  < 0.0001, full squat ( r 2 adj  = 0.95; 95% CI for slope is [−0.0136, −0.0128], P  < 0.0001) and half squat ( r 2 adj  = 0.96; 95% CI for slope is [−0.0116, 0.0124], P  < 0.0001). The 1RM was attained with a MPV and V max of 0.21 ± 0.06 m s −1 and 0.63 ± 0.15 m s −1, 0.29 ± 0.05 m s −1 and 0.89 ± 0.17 m s −1, 0.33 ± 0.05 m s −1 and 0.95 ± 0.13 m s −1 for leg press, full squat and half squat, respectively. Results indicate that it is possible to determine an exercise-specific %1RM by measuring movement velocity for that exercise.